Absence of an association between HLA-DRB1*04 and rheumatoid arthritis in newly diagnosed cases from the community. Issue 7 (July 1993) - Thomson, W; Pepper, L; Payton, A; Carthy, D; Scott, D; Ollier, W; Silman, A; Symmons, D
Abstract : OBJECTIVES--To determine HLA-DR4 and DR1 allele frequencies in a series of patients with newly diagnosed early inflammatory arthritis. METHODS--HLA-DR1 and DR4 frequencies were determined by oligonucleotide typing of 208 patients classified as having either rheumatoid arthritis (RA) or undifferentiated inflammatory polyarthritis. RESULTS--The frequency of occurrence of DR4 in these patients with RA did not differ significantly from that in controls in the United Kingdom (42 v 37%). HLA-DR1 was increased in the group with inflammatory polyarthritis (25 v 18%). CONCLUSIONS--The frequency of DR4 is not increased in newly diagnosed community based patients with RA. This supports the hypothesis that DR4 is less important as a marker for susceptibility to RA than it is for disease persistence or severity.